The Influence Of Products On Customer Decisions Micro Bussiness Credit (KUM) With Promotion as Moderate Variables in PT. Bank Mandiri (Persero) TBK KCP Mandiri Muara Kelingi Kabupaten Musi Rawas In Condition Covid 19 Pandemic - Maya Sari, Wisdalia (Adpebi Science Series, 2022)
The problems in this research are: a). Some SMEs found in the field that the interest rate for KUM products was too high at 1.5% compared to KUR products with 0.27% interest, b). There are still many KUM products offered to customers who do not know, c). The promotions carried out by the Credit Sales Marketig (MKS) are still less than optimal for prospective customers, d). Promotions given by Credit Sales Marketig (MKS) to customers are not optimal, so that customers in making decisions are not optimal. Research results: a). Whereas the influence of the product on the decisions of Micro Business Credit Customers (KUM) at PT. Bank Mandiri (Persero) Tbk. shows that the tcount value is = 3.773 which is greater than the ttable value with a = 5%, df (n-2) = 36–2 = ttable 2.042 with a significant level = 0.000 < (a) 0.05, p. This shows that Ha is accepted and Ho is rejected. So that it can be interpreted that the product partially has an influence on customer decisions at PT. Bank Mandiri (Persero) Tbk., b)the influence of the product on the decisions of Micro Business Credit (KUM) customers with promotion as a moderating variable at PT. Bank Mandiri (Persero) Tbk. After entering the moderating variable (promotion), the R Square value of 0.395 or 39.5% is obtained, an increase of 10% from the result of the R Square value before the moderating variable is 0.295 or 29.5%, so that the moderating variable strengthens the influence of product variables on customer decisions